A Simple Method for Synthesis of High‐Quality Millimeter‐Scale 1T′ Transition‐Metal Telluride and Near‐Field Nanooptical Properties. Issue 38 (21st August 2017) - Chen, Kun; Chen, Zefeng; Wan, Xi; Zheng, Zebo; Xie, Fangyan; Chen, Wenjun; Gui, Xuchun; Chen, Huanjun; Xie, Weiguang; Xu, Jianbin
Abstract : The controlled synthesis of MoTe2 and WTe2 is crucial for their fundamental research and potential electronic applications. Here, a simplified ambient‐pressure chemical vapor deposition (CVD) strategy is developed to synthesize high‐quality and large‐scale monolayer and few‐layer 1T′‐phase MoTe2 (length ≈ 1 mm) and WTe2 (length ≈ 350 µm) crystals by using ordinary salts (KCl or NaCl) as the growth promoter combining with low‐cost (NH4 )6 Mo7 O24 ·4H2 O and hydrate (NH4 )10 W12 O41 · x H2 O as the Mo and W sources, respectively. Atomic force microscopy, X‐ray photoelectron spectroscopy, Raman spectroscopy, and transmission electron microscopy confirm the high‐quality nature and the atomic structure of the as‐grown 1T′ MoTe2 and WTe2 flakes. Variable‐temperature transport measurements exhibit their semimetal properties. Furthermore, near‐field nanooptical imaging studies are performed on the 1T′ MoTe2 and WTe2 flakes for the first time. The sub‐wavelength effects of 1T′‐phase MoTe2 (λp ≈ 140 nm) and WTe2 (λp ≈ 100 nm) are obtained. This approach paves the way for the growth of special transition‐metal dichalcogenides materials and boosts the future polaritonic research of 2D telluride compounds. Abstract : High‐quality and millimeter‐scale two‐dimensional (2D) 1T′‐phase MoTe2 and WTe2 crystals are synthesized through a simplified chemical vapor deposition (CVD) strategy by using green and ordinary salt as a promoter. Near‐field nanooptical studies are performed on the as‐grown 1T′ transition‐metal tellurides for the first time. The sub‐wavelength effects of 1T′‐phase MoTe2 (λp ≈ 140 nm) and WTe2 (λp ≈ 100 nm) are obtained.